Neurotoxicity fingerprinting of venoms using on-line microfluidic AChBP profiling. (15th June 2018) - Slagboom, Julien; Otvos, Reka A.; Cardoso, Fernanda C.; Iyer, Janaki; Visser, Jeroen C.; van Doodewaerd, Bjorn R.; McCleary, Ryan J.R.; Niessen, Wilfried M.A.; Somsen, Govert W.; Lewis, Richard J.; Kini, R. Manjunatha; Smit, August B.; et al.
Abstract: Venoms from snakes are rich sources of highly active proteins with potent affinity towards a variety of enzymes and receptors. Of the many distinct toxicities caused by envenomation, neurotoxicity plays an important role in the paralysis of prey by snakes as well as by venomous sea snails and insects. In order to improve the analytical discovery component of venom toxicity profiling, this paper describes the implementation of microfluidic high-resolution screening (HRS) to obtain neurotoxicity fingerprints from venoms that facilitates identification of the neurotoxic components of envenomation. To demonstrate this workflow, 47 snake venoms were profiled using the acetylcholine binding protein (AChBP) to mimic the target of neurotoxic proteins, in particular nicotinic acetylcholine receptors (nAChRs). In the microfluidic HRS system, nanoliquid chromatographic (nanoLC) separations were on-line connected to both AChBP profiling and parallel mass spectrometry (MS). For virtually all neurotoxic elapid snake venoms tested, we obtained bioactivity fingerprints showing major and minor bioactive zones containing masses consistent with three-finger toxins (3FTxs), whereas, viperid and colubrid venoms showed little or no detectable bioactivity. Our findings demonstrate that venom interactions with AChBP correlate with the severity of neurotoxicity observed following human envenoming by different snake species. We further, as proof of principle, characterized bioactive venom peptides from a viperid ( Daboia russelli ) and an elapid ( Aspidelaps scutatus scutatus ) snake by nanoLC-MS/MS, revealing that different toxin classes interact with the AChBP, and that this binding correlates with the inhibition of α7-nAChR in calcium-flux cell-based assays. The on-line post-column binding assay and subsequent toxin characterization methodologies described here provide a new in vitro analytic platform for rapidly investigating neurotoxic snake venom proteins. Graphical abstract: Highlights: A high throughput in vitro screening strategy for estimating severity and elements of neurotoxicity caused by snake venoms. The microfluidic High Resolution Screening system rapidly generates neurotoxicity fingerprints of venoms. A correlation between neurotoxicity in patients and AChBP affinity profiles measured is demonstrated with 47 snake venoms. The workflow can be extended to include full structural identification and biological assessment of bioactive venom toxins.